Pengaruh E-Service Quality dan E-Trust Terhadap E-Customer Satisfaction - Dwiky Dharmawan; Eman Sulaeman (Peneliti.net, 2023)
The growth in the number of internet users encourages competition for business people to be able to win market competition, especially electronic transaction trading. Customer satisfaction for a company is one of the most important things to consider in the process of building a company's business, especially in terms of service quality and trust. This research was conducted to find out how much influence e-service quality and e-trust have on e-customer satisfaction (study on OVO digital wallet users). This research is in the form of descriptive and verifiable research with a quantitative approach. The sampling technique in this study used Probability Sampling with Simple Random Sampling with a sample of 385 respondents, namely OVO digital wallet users. In this study, a test of the validity of the data and a test of classical assumptions were carried out. The data analysis techniques used are Scale Range Analysis and Path Analysis techniques with the help of Microsoft excel and SPSS. Based on the results of this study indicate that the variable e-service quality and e-trust have a positive and significant effect on e-customer satisfaction.